Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/srep05527
|View full text |Cite
|
Sign up to set email alerts
|

Combining colour and temperature: A blue object is more likely to be judged as warm than a red object

Abstract: It is commonly believed that reddish colour induces warm feelings while bluish colour induces cold feelings. We, however, demonstrate an opposite effect when the temperature information is acquired by direct touch. Experiment 1 found that a red object, relative to a blue object, raises the lowest temperature required for an object to feel warm, indicating that a blue object is more likely to be judged as warm than a red object of the same physical temperature. Experiment 2 showed that hand colour also affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Our findings support the idea that the combination of different features in thermal-tactile perception follows inference processes for the purpose of coherent object perception. Previous work has shown that inferences regarding visual properties change haptic estimates, such as temperature, weight, surface texture and size (Lederman et al, 1986;Ernst and Banks, 2002;Brayanov and Smith, 2010;Ho et al, 2014). TR similarly appears to be driven by a mechanism in which inferences regarding tactile properties change temperature estimates.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our findings support the idea that the combination of different features in thermal-tactile perception follows inference processes for the purpose of coherent object perception. Previous work has shown that inferences regarding visual properties change haptic estimates, such as temperature, weight, surface texture and size (Lederman et al, 1986;Ernst and Banks, 2002;Brayanov and Smith, 2010;Ho et al, 2014). TR similarly appears to be driven by a mechanism in which inferences regarding tactile properties change temperature estimates.…”
Section: Discussionmentioning
confidence: 80%
“…It enables us to perceive the surface and material properties of objects quickly and reliably despite the complexity and objective ambiguities in the environments (Kersten et al, 2004). Previous work has shown that inferences regarding visual properties change haptic estimates, such as temperature, weight, surface texture and size (Lederman et al, 1986;Ernst and Banks, 2002;Brayanov and Smith, 2010;Ho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The link between brightness, saturation and size can be explained by the bodily constraint of a nonuniform distribution of photoreceptors across the retina, resulting in different color vision in the periphery compared to vision in the fovea [24]. The association between physical temperature and hue can be explained by the internalization of correlations between stimuli that are present in the environment (like fire, sun, water) and our bodies (blood circulation) [9]. As predicted, multiple McNemar tests (Bonferroni corrected) revealed no difference between the different hues tested across the weight and size conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In such forced-choice reaction time tasks, the participants' full attention is directed to the target stimuli, thus inverting the prediction. Such inverted color effects are typically found in color psychology when single-color evaluations are extended to more applied contexts and interactions [25], thus questioning the transferability of results of basic research to more applied contexts.…”
Section: Research Question and Scope Of The Empirical Studymentioning
confidence: 97%